ความได้เปรียบในการแข่งขันด้านการท่องเที่ยวของอาเซียนในตลาดนักท่องเที่ยวจีน: The Competitive Advantage in Tourism of ASEAN in Chinese Tourists Market - อั้นทอง อัครพงศ์; ขาวสะอาด มิ่งสรรพ์ (Journal of Applied Economics and Management Strategy, 2018)
การขยายตัวอย่างก้าวกระโดดของนักท่องเที่ยวจีนตั้งแต่ปี พ.ศ. 2553 ส่งผลต่อโครงสร้างตลาดนักท่องเที่ยวในอาเซียนและความได้เปรียบในการแข่งขัน บทความนี้มีวัตถุประสงค์เพื่อเปรียบเทียบความได้เปรียบในการแข่งขันด้านการท่องเที่ยวของประเทศอาเซียนในตลาดนักท่องเที่ยวจีน โดยประยุกต์ใช้อัตราส่วน ความได้เปรียบในการแข่งขันทั้งในเชิงสถิตและพลวัต และการวิเคราะห์การเปลี่ยนแปลงส่วนแบ่งในการศึกษา ข้อมูลจำนวนนักท่องเที่ยวจีนที่เดินทางมาท่องเที่ยวประเทศอาเซียน (ยกเว้น บรูไน) ระหว่างปี พ.ศ. 2546-2557 ผลการศึกษา พบว่า หลังปี พ.ศ. 2552 อาเซียนมีความได้เปรียบในการแข่งขันเพิ่มขึ้นในตลาดนักท่องเที่ยวจีน ไทยและเวียดนามเป็นสองประเทศที่มีความได้เปรียบในการแข่งขันในตลาดนักท่องเที่ยวจีน ประเทศอาเซียนแต่ละประเทศมีแนวโน้มสถานการณ์ตลาดแตกต่างกัน ดังนั้นจึงควรใช้กลยุทธ์การตลาดที่แตกต่างกัน โดยเวียดนาม เมียนมา และสปป. ลาว ไม่จำเป็นต้องเปลี่ยนกลยุทธ์การตลาด สำหรับไทยและกัมพูชาควรทุ่มเทความสนใจในตลาดนักท่องเที่ยวจีนให้มากขึ้น ส่วนสิงคโปร์ควรให้ความสำคัญกับตลาดนักท่องเที่ยวจีนต่อไป ขณะที่ฟิลิปปินส์ อินโดนีเซีย และมาเลเซีย ควรปรับปรุงแผนทางการตลาดใหม่ในตลาดนักท่องเที่ยวจีน อย่างไรก็ตามไทยควรใช้โอกาสการเป็นผู้นำในตลาดนักท่องเที่ยวจีนแสวงหาความร่วมมือและพันธมิตรด้านการท่องเที่ยวภายในภูมิภาค และควรใช้โอกาสจากการเข้าเป็นประชาคมเศรษฐกิจอาเซียน ในการพัฒนาเส้นทางคมนาคมภายในภูมิภาคและกำหนดนโยบายร่วมกันเพื่อส่งเสริมตลาดนักท่องเที่ยวจีนในภูมิภาคอาเซียน The explosive growth of Chinese tourists since 2010 affected the market structure of tourists in ASEAN and the competitive advantage. This article aims to compare the competitive advantage in tourism of ASEAN countries particularly Chinese tourists’ market. Both static and dynamic competitive advantage ratio (CAR) and shift-share analysis (SSA) are applied to analyze the Chinese tourists’ arrival to ASEAN countries (except Brunei) during 2003-2014. The results show that, after 2009 ASEAN has more competitive advantage in Chinese tourists’ market. Thailand and Vietnam are two countries, which have the competitive advantage in Chinese tourists’ market. Each of ASEAN countries has different market trend. Hence, it should have different marketing strategies. Vietnam, Myanmar and Lao PDR should not change their marketing strategies. Thailand and Cambodia should give more specific attention in Chinese tourists market. Singapore should sustained attention, whilePhilippines, Indonesia, and Malaysia should re-design their marketing strategies in Chinese tourists’ market. However, Thailand should use its advantage as the leader in Chinese tourists’ market to build alliance and foster intra-regional collaboration in tourism. Moreover, Thailand should use the opportunity as a member of ASEAN Economics Community (AEC) to develop a transportation route within the region and to design an alliance policy for promoting Chinese tourists’ market in the ASEAN.